RANCANGAN ARDUINO UNO PADA MESIN PEMARUT DAN PEMERAS KELAPA - Fikri, Muhammad; Arifin, Zaenal (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2023)
The Arduino Uno is a device commonly used as the brain of a control system. It utilizes an Integrated Circuit (IC) known as the ATMega328P. The Arduino Uno comes equipped with a user-friendly programming environment, making it suitable for both beginners and experienced developers. It finds applications in various devices, such as the Coconut Grater and Coconut Squeezer machines. In the case of these machines, the Arduino Uno is employed to control the direction of the Coconut Squeezer's motor rotation and the activation of the Coconut Grater's motor using buttons. The objective of this journal is to identify the components used for controlling input/output and to understand the programming techniques for the Arduino Uno. The findings from this journal provide insight into the components utilized in the Coconut Grater and Coconut Squeezer machines and serve as a blueprint for their construction. This design aims to ensure the precise control of the Coconut Grater and Coconut Squeezer machines.